1775 Conn. Acts 413 - (:unkn) unknown (My University, 1775)
Provided that a sufficient supply of arms to be procured for the benefit of inhabitants of households and other persons not on the militia roll. Every person for whom any arm shall be impressed shall be paid four shilling for its use. Users shall be fined four shilling if they lose the arm.
Keywords: REQUIRED POSSESSION